2020
DOI: 10.4103/jfmpc.jfmpc_646_20
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of cardiovascular risk in a rural population of Lucknow district using WHO/ISH risk prediction charts

Abstract: Context: Cardiovascular diseases (CVDs) are the number one cause of death globally, with low- and middle-income countries being affected disproportionately. By 2020, it is projected that there will be 25 million deaths from CVD worldwide, 19 million of which would be from middle- and low-income countries. Aims: The aim of this study was to estimate the 10-year risk of cardiovascular events among adults aged ≥40 years in a rural population of Lucknow district using the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Similar findings were observed in the study done by Deori T J et al in rural population of Lucknow and Balaji B V et al in rural population of India. [18,19] The risk of developing CVD increases as age progress, which was found in this study. The intermediate and high CVD risk was more among study participants who were above 40 years irrespective of genders.…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings were observed in the study done by Deori T J et al in rural population of Lucknow and Balaji B V et al in rural population of India. [18,19] The risk of developing CVD increases as age progress, which was found in this study. The intermediate and high CVD risk was more among study participants who were above 40 years irrespective of genders.…”
Section: Discussionsupporting
confidence: 75%
“…It was observed that there was a high concordance of 83.3% between the laboratory-based and non-laboratorybased CVD risk charts. 2013) respectively [13][14][15]. In our study, the kappa statistic between the two WHO CVD risk charts was 0.64.…”
Section: Discussionmentioning
confidence: 46%
“…There are previous studies assessing the concordance of WHO/ISH risk prediction tool between the charts with cholesterol and without cholesterol levels, which reported concordance in the range of 86.3% to 89.5%. A study by Deori et al (2020) observed a concordance of 86.3% while concordance of 89.5% and 88.1% was observed by Fatema et al (2015) and Nordet et al (2013) respectively [ 13 14 15 ]. In our study, the kappa statistic between the two WHO CVD risk charts was 0.64.…”
Section: Discussionmentioning
confidence: 91%
“…in the rural part of South India (25.2%). (20,21) Contrary to this, Ghorpade AG et.al. have shown only 17% of the participants at moderate to high risk for the occurrence of cardiovascular events by using WHO/ISH risk prediction charts in a rural population of South India (22).…”
Section: Resultsmentioning
confidence: 93%